FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MEMILIH SEKOLAH MENENGAH KEJURUAN (SMK) NURUL FALAH PEKANBARU - Nuraisyah '; Gimin '; RM.Riadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aimed to determine the factors that influence consumer behavior in choosing a vocational high school in SMK Nurul Falah Pekanbaru. The research was conducted at SMK Nurul Falah Pekanbaru. The population of this study were students of SMK Nurul Falah Pekanbaru academic year 2012/2013 up to 2014/2015 which amounted to 532 people. The sample used by the Gay opinion proportionate stratified random sampling method. The sample size of 53 people. Data analysis technique used is multiple regression. The results of this study show that: 1) Pricing and Facilities significantly to the influence on consumer behavior in choosing a vocational school Nurul Falah Pekanbaru. 2) Product, Promotion, and location does not significantly influance the behavior of consumers in choosing a vocational school Nurul Falah Pekanbaru.Key words: Consumer Behavior, Price, Product, Promotion, Location, Facilities